Электромагнитная совместимость при работе группы кранов с частотно-регулируемыми приводами - Андриенко, Петр Дмитриевич; Немыкина, Ольга Владимировна; Андриенко, Андрей Андреевич; Авдеев, Игорь Викторович; Прихно, Валерия Леонидовна (НТУ "ХПИ", 2019)
В статье приведены результаты исследований электромагнитной совместимости систем питания кранов с частотно-регулируемыми приводами в режимах потребления и рекуперации энергии приих одновременной работе. Показано, что при одновременной работе показатели электромагнитной совместимости ухудшаются, что требует установки дополнительных групповых фильтров.

The article presents the results of electromagnetic compatibility’s research of power supply cranes’ systems with variable frequency drives in the modes of consumption and energy recovery by their simultaneous operation. It is shown that the installation individual filters on cranes with a frequency-variable drive, providing electromagnetic compatibility with a power source, does not allow to obtain satisfactory compatibility by group work of cranes. This circumstance is caused by the influence of variable and non-linear of trolley conductors in the power supplycircuits of individual cranes on the magnitude of the voltage loss, power factor, current distortion factorand voltage distortion factor.
Electromagnetic compatibility in operation of group cranes with variable frequency drive
Keywords: высшие гармоники; потери напряжения; токопроводы; алюминиевые шины; активный выпрямитель; системы питания кранов; higher harmonics; voltage loss; conductors; aluminum tires